2020
DOI: 10.1101/2020.04.06.20055194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute kidney injury in patients hospitalized with COVID-19 in Wuhan, China: A single-center retrospective observational study

Abstract: evaluated the association between changes in the incidence of AKI and COVID-19 disease and clinical outcomes by using logistic regression models. Results:A total of 287 patients, 55 with AKI and 232 without AKI, were included in the analysis.Compared to patients without AKI, AKI patients were older, predominantly male, and were more likely to present with hypoxia and have pre-existing hypertension and cerebrovascular disease. Moreover, AKI patients had higher levels of white blood cells, D-dimer, aspartate ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2
4

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 10 publications
2
35
2
4
Order By: Relevance
“…At variance with previous findings where AKI was more represented among males [28], we did not find a significant difference in sex distribution among our AKI patients. Similarly, the use of ACE-Is or ARBs was not associated with an increased risk of AKI at multivariate analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…At variance with previous findings where AKI was more represented among males [28], we did not find a significant difference in sex distribution among our AKI patients. Similarly, the use of ACE-Is or ARBs was not associated with an increased risk of AKI at multivariate analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings from our study are in consonance with those from prior studies suggesting that AKI is a significant risk factor of clinical deterioration and in-hospital death among COVID-19 patients [3,4,6,26]. Patients who developed HA-AKI had poorer outcomes than those with CA-AKI.…”
Section: Color Version Available Onlinesupporting
confidence: 91%
“…In another retrospective study of 333 patients, about 75% experienced urine dipstick abnormalities or AKI (40). In the first studies during the pandemic spread, incidence of AKI was reported from 3 to 9% of patients, but more recent studies reported an incidence rate of 15% (17,41). In one observational study of 5,449 hospitalized patients, the incidence of AKI was 36.6 with 14.3% of patients requiring dialysis and was even higher in patients admitted to the ICU (42).…”
Section: Kidney Involvement During Covid-19mentioning
confidence: 98%
“…In a single-center, retrospective, observational study of 287 patients, 55 patients presented with AKI as defined by the Kidney Disease Improving Global Outcomes (KDIGO). These patients were significantly older, more likely male, and with other comorbidities, including chronic renal insufficiency, hypertension, and cerebrovascular disease, and tended to have more severe pneumonia (not peer-reviewed) (41). Of these patients, 14.3% presented with AKI at stage 1, while 4.9% of patients presented with stage 2 or 3 (41).…”
Section: Kidney Involvement During Covid-19mentioning
confidence: 99%